Use of Mesenchymal Stromal Cells for Recovery of Cartilage Tissue - Volkova, N. O.; Goncharuk, O. I.; Zasadnyuk, I. A.; Filippova, M. S.; Gryschenko, V. I. (Problems of Cryobiology and Cryomedicine, 2008)
In this work possible marrow mesenchymal stromal cell application was estimeted for cartilage tissue renewal. Two models of cartilage injury with different localization were considered, they were namely the defect of articular cartilage and degenerative intervertebral damage. It was shown that cell therapy application in an experiment led to damaged tissue renewal.